2018
DOI: 10.1007/s10597-018-0269-1
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Peer-Delivered Parenting Skills Programs Across New York State

Abstract: Peers are an important adjunct to the public mental health service system, and are being increasingly utilized across the country as a cost-effective solution to workforce shortages. Despite the tremendous growth of peer-delivered support over the past two decades, it has only been within the past few years that peer programs have been the subject of empirical inquiry. The purpose of this study was to examine the prevalence and characteristics of peer-delivered parenting programs across the New York State publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The targeted skills and processes are referred to in the curriculum as the 4 Rs and 2 Ss. Prior studies of the 4 Rs and 2 Ss model found that the intervention was associated with improvements in children’s behavior, caregiver depression and stress, and high attendance rates (Acri, Chacko, Gopalan, & McKay, 2018a; Acri, Craig, & Adler, 2018b; Chacko et al, 2015; Gopalan et al, 2015; McKay et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…The targeted skills and processes are referred to in the curriculum as the 4 Rs and 2 Ss. Prior studies of the 4 Rs and 2 Ss model found that the intervention was associated with improvements in children’s behavior, caregiver depression and stress, and high attendance rates (Acri, Chacko, Gopalan, & McKay, 2018a; Acri, Craig, & Adler, 2018b; Chacko et al, 2015; Gopalan et al, 2015; McKay et al, 2011).…”
Section: Methodsmentioning
confidence: 99%